Growth of Glycine Barium Nitrate (GBN) Crystal via Slow Evaporation Method Accompanied by the Application of External Electric Field - P S E Adistha Putra Adistha Putra (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2020)
Glycine Barium Nitrate (GBN) crystals were grown by slow evaporation method accompanied by the application of an external electric field. The application of external electric field in crystal growth system is expected to align local dipole moments, therefore, it could be expected that it will increase the quality of the grown single crystal. GBN crystals were grown from their saturated solution with slow evaporation method in Pyrex glass tube that was connected with a high voltage power supply (15 kV). Crystal grew over a span of 16-28 days at 50 oC with a variation of electric field 0-5 kV/cm. Grown GBN single crystals has tr apezoid-shaped, with an typical dimension of 5x4x3 mm3. GBN crystals grown with various electric field were characterized with X-Ray powder diffraction method and it was found that higher electric field can cause GBN diffraction peaks shifting to lower 2θ. GBN adopt orthorhombic crystal lattice with space group P212121. Refinement analysis have been carried out with Le Bail Method using Fullprof program. Results of refinement indicated that lattice parameter a become longer, while b and c decreases along with the increasing of electric field application. The crystal lattice parameter a for GBN 0 kV / cm, 1 kV / cm, 2 kV / cm, 3 kV / cm, 4 kV / cm and 5 kV / cm are 8,2328 (3) Å; 8,2510 (2) Å; 8,2557 (1) Å; 8,2571 (1) Å; 8,2623 (2) Å; and 8,2574 (2) Å respectively, while the lattice parameter b and c were decreased as applied electric field increased.